An Identification of Landslide Potential Areas by Using the Shuttle Radar Topography Mission (SRTM) Images - Rahma Hi Manrulu; Aryadi Nurfalaq (Faculty of Engineering, Malikussaleh University, 2018)
This study aims to identify slope conditions along the shaft roads of Palopo-North Toraja using SRTM imagery related to landslide potential areas. The method used in identifying these areas comprises two approaches utilizing satellite imagery and field surveys. SRTM images are proposed to satellite imagery which was analyzed spatially by using the slope feature in the arc toolbox ArcGIS. On the other hand, field surveys were carried out by observing 19 location points which were used as observation stations in terms of recording coordinates and description of land cover, slope and landslide potential area. As the results, areas that experience cracks (landslide crawling) are founded from flat-slope to low-slope areas whereas medium-slope locations at 35,9% up to high-slope locations around 72,5% are landslides potential areas with the type of translation avalanche.